Characterization Method of Biological Functionalization Process of Silicon Surface Based on Cantilever Biosensor. Issue 208 (12th June 2020) - Wang, Jingjing; Zhang, Li; Cao, Houyong; Zhu, Yinfang; Yang, Jinling; Gu, Erdan
Abstract: A novel cantilever array-based biosensor was batch-fabricated with IC compatible MEMS technology for precise liver cancer biomarker detection. A microcavity was designed in the free end of the cantilever for local antibody-immobilization using the micro-printing system, which can dramatically reduce the effect of adsorption-induced stiffness coefficient k variation. These structural features offer several advantages: high sensitivity, high throughput, high mass detection accuracy, and high specification. In addition, the surface biofunctionalization methods were commonly used in biological detection devices are mainly introduced, and the optimal biofunctionalization scheme for silicon-based microcantilever is proposed. The modification procedure of APTES-GA was characterized by cantilever, and the uniform aldehyde surface of the microcantilever was obtained. The immobilization time and culture method of the microcantilever antibodies were optimized to obtain localized, dense and highly active antibody surfaces. Which provides an excellent surface functionalization method for the cantilever biosensor.